2018
DOI: 10.1002/jcph.1255
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Efficacy and Safety of Commonly Prescribed Drugs and Effect of These Drugs on Quality of Sleep in Patients Suffering From Zoster‐Associated Pain

Abstract: This observational, prospective, single-center study was conducted to evaluate the efficacy and safety of commonly prescribed drugs for zoster-associated pain and their impact on quality of sleep at a tertiary care hospital in western India. Patients ≥18 years of age, newly diagnosed with zoster-associated pain were evaluated on days 0, 7, 14, 30, 60, 90, 120, 150, and 180 or until resolution of pain, whichever was earlier, using the Wong Baker FACES Pain Rating Scale, Neuropathic Pain Scale, and Insomnia Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition, nerve block, intrathecal glucocorticoid injection, local botulinum toxin A injection, pulsed radiofrequency, spinal cord stimulation, dorsal root ganglion stimulation, and physical therapy are routine treatments for PHN [8,9,46,47]. Thoracic and cervical dermatome involvement is reportedly most common in patients with HZ [48,49]. TPVB can produce ipsilateral somatosensory and sympathetic nerve blockade in the thoracic dermatome; therefore, it is an ideal and effective therapy for the treatment of acute thoracic HZ pain and PHN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nerve block, intrathecal glucocorticoid injection, local botulinum toxin A injection, pulsed radiofrequency, spinal cord stimulation, dorsal root ganglion stimulation, and physical therapy are routine treatments for PHN [8,9,46,47]. Thoracic and cervical dermatome involvement is reportedly most common in patients with HZ [48,49]. TPVB can produce ipsilateral somatosensory and sympathetic nerve blockade in the thoracic dermatome; therefore, it is an ideal and effective therapy for the treatment of acute thoracic HZ pain and PHN.…”
Section: Discussionmentioning
confidence: 99%
“…Another very frequently found combination is the one between gabapentinoids and antidepressants [61,63]. In fact, combinations of PGB/GBP and DXT/TCAs have been previously recommended for consideration as an alternative to increasing dosages in monotherapy for patients unresponsive to monotherapy with moderate dosages [8].…”
Section: Gabapentinoids and Antidepressants In Combinationmentioning
confidence: 99%
“…Combinations of analgesics used simultaneously in acute pain have been demonstrated to provide additive pain relief [74,75], and combination analgesics are among the most effective drugs in acute pain [76]. Given the evidence that a considerable number of patients with NP receive two or more drugs [61,63], we were only able to identify 16 recent relevant citations for this review and only 6 high-quality NP RCTs that evaluated the strategy of CT. Even more surprisingly, almost 10 years after the last review was published [27], these problems have not been addressed, and clinicians still need to rely on low-quality evidence and empirical knowledge when it comes to prescribing CT for NP.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Another very frequently found combination is the one between gabapentinoids and antidepressants [61,63]. In fact, combinations of PGB/GBP and DXT/TCAs have been previously recommended to be considered as an alternative to increasing dosages in monotherapy for patients unresponsive to monotherapy with moderate dosages [8].…”
Section: Gabapentinoids and Antidepressants In Combinationmentioning
confidence: 99%
“…It has been demonstrated that combinations of analgesics used simultaneously in acute pain provide additive pain relief [74][75], and combination analgesics are among the most effective drugs in acute pain [76]. Given the evidence that a considerable number of patients with NP receive two or more drugs [61,63], we were only able to identify 16 recent relevant citations for this review and only 6 high-quality NP RCTs that evaluated the strategy of CT. It is even more surprising that, almost 10 years after the last review was published [27], these problems have not been addressed and clinicians still need to rely on low-quality evidence and empirical knowledge when it comes to prescribing CT for NP.…”
Section: Implications For Clinical Practicementioning
confidence: 99%